Simulating collective behavior in the movement of immigrants by using a spatial prisoner’s dilemma with move option - Lin, Bingchen; Zhou, Can; Hua, Zhe; Hu, Guangdi; Ding, Ruxin; Zeng, Qiyuan; Li, Jiawei (Springer, Singapore, 2020)
The movement of immigrants is simulated by using a spatial Prisoner’s Dilemma (PD) with move option. We explore the effect of collective behavior in an evolutionary migrating dynamics. Simulation results show that immigrants adopting collective strategy perform better and thus gain higher survival rate than those not. This research suggests that the clustering of immigrants promotes cooperation.